From experience to scene: Creation of festive characters. Case study - Character Quinde Colibri. (The Voz a Vos Bulletin, 2026)
This presentation presents the process of creation and evolution of the character Quinde Hummingbird in the play Rumba Vital, a free version of Rumba Vida del Teatro Taller de Colombia, developed as part of the course Montaje Interdisciplinar Teatro, Fiesta y Carnaval 2025-I of the Licentiate in Performing Arts of the University Antonio Nariño.This research is situated in the field of research-creation and aims to present the artistic-pedagogical experiences that contributed to the construction of this festive character.The importance of experiential processes in the formation of master artist researchers is highlighted, understanding the carnival not only as a cultural manifestation, but as a pedagogical, political and creative space.
Keywords: Festive theater; Character; Artistic experience; Carnival; Research-creation